2023
DOI: 10.1186/s12964-023-01062-y
|View full text |Cite
|
Sign up to set email alerts
|

Opposite and dynamic regulation of the interferon response in metastatic and non-metastatic breast cancer

Abstract: Background To our current understanding, solid tumors depend on suppressed local immune reactions, often elicited by the interaction between tumor cells and tumor microenvironment (TME) components. Despite an improved understanding of anti-cancer immune responses in the TME, it is still unclear how immuno-suppressive TME are formed and how some cancer cells survive and metastasize. Methods To identify the major adaptations that cancer cells underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Therefore, the effect of IFN on retrotransposons could be related to the hormone-regulated microenvironment and might be tumor type-specific. The context-dependent IFN signaling associated with the ER+ and ER-negative breast cancer subtypes, which impacts their response to therapy and overall outcomes, reinforces the above notion [152]. It could be interesting to extend these experiments to identify the levels of retrotransposon expression among ER+ and ERbreast tumors.…”
Section: Immune Signature Of Retrotransposons In Cancermentioning
confidence: 63%
“…Therefore, the effect of IFN on retrotransposons could be related to the hormone-regulated microenvironment and might be tumor type-specific. The context-dependent IFN signaling associated with the ER+ and ER-negative breast cancer subtypes, which impacts their response to therapy and overall outcomes, reinforces the above notion [152]. It could be interesting to extend these experiments to identify the levels of retrotransposon expression among ER+ and ERbreast tumors.…”
Section: Immune Signature Of Retrotransposons In Cancermentioning
confidence: 63%
“…However, this is the first time that it has been identified as a potential biomarker associated with the Basal A subtype. Recently, Lamsal et al 88 demonstrated that IFIT3 mRNA and its protein are highly expressed in human metastatic breast cancer cell line MDA-MB-231, while its expression is low in non-metastatic MDA-MB-453 cell line. The next hub gene, PSMB9 , encodes a modified enzyme with peptidase activity involved in the proteasome pathway, which helps cells deal with oxidative and proteotoxic stress.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that IFN1 signaling induces the expression of pro-apoptotic, anti-angiogenic, and immunomodulatory genes that could be used in therapy against cancers and infectious diseases. In randomized trials, administration of IFN1 ligands resulted in the upregulation of estrogen receptors (ERs) in breast cancer tumor cells that would make them sensitive to ER-targeted therapies [26] . However, examination of IFN1 signaling in cancer cells is insufficient to determine breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%